Enhancing source identification of water-soluble heavy metal contamination in urban road sediments: a receptor model approach for water and sediment quality in a Chinese metropolitan area - Muhammad Faisal; Zai-Jin You; Noman Ali Buttar; Muhammad Naeem; Muhammad Imran Azam; Basharat Ali; Abeer Hashem; Khalid F Almutairi; Elsayed Fathi Abd_Allah (Environmental Research Communications)
This study investigates the concentrations and sources of 8 heavy metals in urban road sediments and a total of 116 samples were collected from 29 locations, with four samples per location from Zhengzhou, China. Pb concentrations significantly exceeded background values, while Hg levels showed variability across locations. Pollution indices reveal that Cu and Cd, two hazardous metals, contribute significantly to urban road dust pollution. Notably, Hg shows high contamination levels, while Pb and Cr exhibit moderate contamination. The measured concentrations of the heavy metals are: Cr (28.32 μg l ^–1 ), Cu (334.65 μg l ^–1 ), Cd (2.87 μg l ^–1 ), Ni (83.20 μg l ^–1 ), Zn (204.10 μg l ^–1 ), As (45.10 μg l ^–1 ), Pb (4.11 μg l ^–1 ), and Hg (0.27 μg l ^–1 ). Using principal component analysis (PCA), three primary components (PC1, PC2, and PC3) were identified, explaining 86.85% of the variance in heavy metal concentrations. PC1, dominated by Cr and Pb, suggests industrial activities as the main source. PC2, influenced by As and Cd, reflects pollution from agrochemical use, while PC3, with high Ni values, indicates sources from alloy production and electroplating processes. These findings highlight the urgent need for targeted environmental management strategies to mitigate the health and ecological risks posed by heavy metal contamination in urban environments.